THE EFFECTIVENESS OF THE SCRAMBLE METHOD TO IMPROVE THE STUDENTS’ ABILITY IN READING ALOUD AT GRADE II ELEMENTARY SCHOOLS - Yeni Sulaeman; Muhardila Fauziah; Aan Aan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The purpose of this study was to improve the students' ability in reading aloud by using the scramble method and to find out the students' sentence comprehension skills. This research wa a classroom action research conducted in two learning cycles. Each cycle consisted of two meetings with 2x30 minutes each. The data were obtained by observing the learning process, learning activities, and the results of the reading aloud comprehension test. The results showed that the students' ability to read aloud at grade II increased after the imlementation of scramble method in the learning process. Then, the results of the observation in the first cycle found several shortcomings so that they affected the students’ learning activities. The tests given at the second meeting were categorized as fairly good. After that, in the second cycle, the learning process became more conducive and fun. The students became active and enthusiastic about the learning process. It was found that 95% of students actively participated in learning and the average score of the test was 93.50 with very good category. Thus, the implementation of scambel method improved the students’ ability to read aloud at grade II SDN Nameng 1 Rangkasbitung.